Unlocking Market Opportunities: The Impact of Sustainable Energy Practices on SME Competitiveness - Ezinne C. Chukwuma-Eke; Verlinda Attipoe; Comfort Iyabode Lawal; Solomon Christopher Friday; Ngozi Joan Isibor; Abiola Oyeronke Akintobi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This paper explores the impact of sustainable energy practices on the competitiveness of small and medium-sized enterprises (SMEs), focusing on the strategic advantages of adopting renewable energy solutions and energy-efficient technologies. In light of rising energy costs, environmental regulations, and consumer demand for sustainability, SMEs are increasingly turning to sustainable energy as a means of reducing operational costs, differentiating themselves in the market, and ensuring regulatory compliance. Through a comprehensive analysis of key theories on competitive advantage and sustainability, the paper demonstrates how integrating sustainable energy practices can lead to significant cost savings, enhanced brand value, and a stronger market position. It also examines the barriers SMEs face in adopting these practices, including financial constraints, technological gaps, and regulatory challenges. To overcome these obstacles, the paper highlights the role of financial institutions, policymakers, and strategic frameworks in providing SMEs with the necessary support, including targeted financing options and policy incentives. The findings emphasize that while adopting sustainable energy practices offers substantial benefits for SMEs, overcoming existing barriers requires collaboration between the public and private sectors to create a more conducive environment for clean energy investment. Finally, the paper provides recommendations for future research into emerging technologies and sector-specific sustainable energy solutions, suggesting that these innovations could further enhance SME competitiveness in an evolving global marketplace.